2021
DOI: 10.3390/biom11030450
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Far-Red Light Supplementation on Hormonal Responses to Cold Acclimation in Barley

Abstract: Cold acclimation, the necessary prerequisite for promotion of freezing tolerance, is affected by both low temperature and enhanced far-red/red light (FR/R) ratio. The impact of FR supplementation to white light, created by artificial LED light sources, on the hormone levels, metabolism, and expression of the key hormone metabolism-related genes was determined in winter barley at moderate (15 °C) and low (5 °C) temperature. FR-enhanced freezing tolerance at 15 °C was associated with promotion of abscisic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 100 publications
3
14
0
Order By: Relevance
“…Prolonged acclimation (21 d) of Carpobrotus edulis plants at 5 °C results in the increase of endogenous contents of trans-zeatin and trans-zeatin riboside (Fenollosa et al, 2018). Acclimation of barley plants at 5 °C during 7 d is accompanied by a decrease in the transzeatin content and an increase in cis-zeatin (Ahres et al, 2021). In winter wheat, elevation in active cytokinins content has been found during 7-31 d of acclimation at 4 °C after its transient drop at the alarm phase of stress response (Vanková et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged acclimation (21 d) of Carpobrotus edulis plants at 5 °C results in the increase of endogenous contents of trans-zeatin and trans-zeatin riboside (Fenollosa et al, 2018). Acclimation of barley plants at 5 °C during 7 d is accompanied by a decrease in the transzeatin content and an increase in cis-zeatin (Ahres et al, 2021). In winter wheat, elevation in active cytokinins content has been found during 7-31 d of acclimation at 4 °C after its transient drop at the alarm phase of stress response (Vanková et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the combination of dark and cold arrests the growth of Arabidopsis plants and leads to a strong decrease of cytokinin levels (Prerostova et al, 2021). Treatment of young barley plants with far-red light stimulates better cold acclimation and is associated with significant changes in phytohormone balance, in particular, an increased ciszeatin concentration (Ahres et al, 2021). Unfortunately, in most studies of plant adaptation to cold stress, the role of light is often not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…To improve postharvest chilling tolerance several studies have investigated the use of pre-harvest light treatments such as modifying the light spectrum to increase the percentage of blue (400-500 nm) and far-red (FR, 700-800 nm) light (Affandi et al, 2020(Affandi et al, , 2022Kovács et al, 2020;Ahres et al, 2021). In this thesis it was investigated if light intensity and spectra influenced chilling tolerance.…”
Section: Can Pre-harvest Light Improve Postharvest Chilling Tolerance?mentioning
confidence: 99%
“…The involvement of far-red (FR) light in acclimation to chilling has gained increasing interest. Most authors relate the proposed mechanism of FR to the induction of the C-repeat-binding factors CBF pathway which function upstream of the cold responsive (COR) genes (Franklin and Whitelam, 2007;Wang et al, 2016a;Ahres et al, 2021). COR genes have a vast function in plants such as inducing enzymes for the biosynthesis of osmoprotectants and proteins related to lipid metabolism (Liu et al, 2019).…”
Section: The Effect Of Far-red Light On Chilling Tolerancementioning
confidence: 99%
See 1 more Smart Citation